32.5k views
3 votes
Simplify the expression.
sec x/tan x

Simplify the expression. sec x/tan x-example-1

1 Answer

4 votes

Answer:

Option b

Explanation:

We know that, by definition:


secx = (1)/(cosx)

We also know that:


tanx = (sinx)/(cosx)

Applying these identities we can simplify the given expression


(secx)/(tanx) = ((1)/(cosx))/((sinx)/(cosx))\\\\(secx)/(tanx) = (cosx)/(sinxcosx)\\\\(secx)/(tanx) = (1)/(sinx)

We know that, by definition:


(1)/(sinx) = cscx

User Bahramdun Adil
by
5.5k points